Devotion, Paintings, and the House: The Collections of Ercole and Giuseppe Branciforti, Princes of Scordia (Palermo, 1687–1720) - Valeria Viola (Religions, 2020)
This paper interrogates familial devotion and its relationship with parts of the house other than the chapel. In detail, it aims to problematize the issue of the devotional/non-devotional use of paintings inside the house by moving the focus from this dual opposition to the active role of canvases, broadly defined. Informed by Jacques Derrida’s and Pierre Bourdieu’s writings, this paper argues for the structural nature of the paintings inside the house and their meaningful correlation with both the arrangement of the domestic interior and the practices of people experiencing those spaces. To do this, the paper challenges the overwhelming attention paid by early-modern scholars to Northern and central Italy and investigates a precise case study, i.e., Palazzo Scordia in Palermo (Sicily). The research draws upon primary sources and amongst these, upon two detailed inventories of furniture referring to two subsequent generations of an aristocratic clan residing in Palermo between the seventeenth and the eighteenth century, i.e., Ercole and Giuseppe Branciforti, princes of Scordia.